MISSED OPPORTUNITY: CANADA'S RE-ENGAGEMENT WITH LATIN AMERICA AND THE CARIBBEAN. - SHAMSIE, YASMINE; GRINSPUN, RICARDO (Canadian Journal of Latin American & Caribbean Studies (Canadian Association of Latin American & Caribbean Studies (CALACS)), 2010)
In 2007, Canada announced it was making Latin America and the Caribbean a foreign policy priority. This article provides an initial assessment of Ottawa's re-engagement with the region, focusing on the tensions associated with its stated position on democracy, human rights, and poverty reduction and its continued adherence to a neoliberal policy set. It argues that support for this economic template, coupled with the fact that Ottawa's relations with the region are governed by, and regularly subverted to, powerful economic and security interests—strategic alignment with U.S. hemispheric priorities would fall in this category—undermine its efforts to address social and democratic development goals in the region. The "pink tide" that is sweeping the region and the efforts by governments of various stripes to find their distinct responses to the social, economic, and ecological crises that envelop the region make Ottawa's free-trade-driven approach seem tired and out of step with sentiments and circumstances in the region.